Figurative Language in the Poem Menggapai Impian by Ni Nengah Restari - Putra, Shiva Dermawan; Tawami, Tatan (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2024)
This study is significant as it aims to discover the meaning behind the figurative language used in the poem “Menggapai Impian” by Ni Nengah Restari. Figurative language, which includes simile, metaphor, personification, hyperbole, alliteration, and metonymy, is used in the analysis as it is commonly found in literature. The data for this study was taken from an E-book named 'Goresan Pena (Antologi Puisi Pendidikan)' by Ni Nengah Restari, dkk 2020. The study reveals that hyperbole is the poem's most frequently used figurative language, followed by personification and metaphor, then Metonymy and Alliteration. By analyzing figurative language in the poem “Menggapai Impian” by Ni Nengah Restari, it enhances the reader’s appreciation and understanding of the poem’s depth and meaning of this poem Keywords: Figurative language, Poem, Ni Nengah Restari